Pengaruh Belanja Daerah Terhadap Kemiskinan Di Provinsi Aceh - Dilla Artika Yelfi; Dwirani Puspa Artha (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the effect of social assistance expenditure, Gross Regional Domestic Product (GRDP), health measured by Life Expectancy (LE), and unemployment measured by the Open Unemployment Rate (OUR) on poverty levels in Aceh Province during the 2014–2023 period. Poverty levels were measured using the percentage of the poor population as the main indicator. The method employed was panel data regression analysis. The results indicate that social assistance expenditure has a positive but insignificant effect on poverty. GRDP and health have a negative and significant effect, indicating that improvements in GRDP and life expectancy can significantly reduce poverty levels. Meanwhile, unemployment has a positive but insignificant effect on poverty. These findings highlight that the health sector has the most effective role in reducing poverty compared to other variables.